BRAINWAVES OF EMOTION AMONG JAPANESE EFL LEARNERS AS PROOF OF THE EFFECTIVENESS OF FAMILY ENVIRONMENT MODE APPROACH (FEMA) - Ocampo, Merissa Braza (PEOPLE: International Journal of Social Sciences, 2016)
This paper expands the author’s recently developed EFL teaching method, the Family Environment Mode Approach (FEMA) (Ocampo, 2016), including students’ narrated endorsements, which give further insight into students learning experience in support of the method’s efficacy. The paper demonstrates that to surrender to the belief that someone has no ability to improve their English fluency obscures the heterogeneity of pathways leading to a thriving learning experience. The idea that failure is often a necessary prerequisite to success is emphasized. The study demonstrates that a combination of changing students’ mindsets to become pro-failure and FEMA is effective in helping them improve their speaking ability, and freeing them from what can seem to be a ‘cage of fear’ with regards to making mistakes. A move from a traditional classroom situation, to one where failure is embraced is shown to be a process that can alleviate or perhaps eradicate anxiety and stress, opening up the gateway of learning. The use of Necomimi (brainwave cat ears) is incorporated to help demonstrate the effectiveness of FEMA. Necomimi is a sophisticated, animatronic cat-ear headset that moves in various ways in response to how the device interprets students’ mood, measuring the brainwaves of emotion while speaking English. The paper reports that strong student support for this method was observed. At the end of the school year, most of the participating students recommended that teachers of English and other subjects adopt FEMA more widely.